Papan Permainan Sebagai Media Komunikasi Visual Mencegah Hipertensi Dengan Pisang Ambon Kuning Bagi Remaja 17-25 tahun di Kota Palembang - Adelia Pratiwi, Elza; Halim, Bobby; Patriansah, Mukhsin (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Hypertension is a condition where blood pressure increases in the body, a person is declared hypertensive if the blood pressure is above 120/80mmHg. Factors that cause hypertension are unhealthy eating patterns and bad lifestyle habits. Most teenagers have bad lifestyle habits and eating patterns, such as smoking, alcohol consumption, excess caffeine and salt, making them susceptible to hypertension. One fruit that contains potassium which is good for preventing hypertension is the Yellow Ambon Banana. The main problem in this design is the lack of knowledge among teenagers regarding the benefits of consuming yellow Ambon bananas which can prevent hypertension. The main aim of this design is to provide important information about hypertension which can be prevented by consuming yellow Ambon bananas for the target audience, namely teenagers 17-25 years. In the media design process, the method used is design thinking which consists of 5 stages, namely Empathize, Define, Ideate, Prototype, and Test. The main media used are the Game Board and Tensimeter. Through this design, it is hoped that teenagers will be able to find out information related to preventing hypertension with yellow Ambon bananas and can prevent the occurrence of hypertension from adolescence